Additive engineering for Sn-based PSCs: Enhancement of open-circuit voltage and fill factor. (15th January 2021) - Chen, Qin; Bai, Luyun; Tsiba Matondo, Jadel; Deng, Minghan; Malouangou Maurice, Davy; Guli, Mina
Abstract: Perovskite solar cells (PSCs) have drawn much attention recently because of their outstanding photo-electrical performance, especially lead halide perovskites. However, the high toxicity of lead contained in perovskite severely hinders further development of the devices in industrial production and commercial applications. As a result, Tin, as one of the non-toxic metal elements exhibiting similar electronic properties with Pb, has been considered as the most suitable ions to substitute toxic Pb in PSCs. However, Sn-based PSCs also face serious challenges such as high intrinsic defects density which mainly originates from Sn 2+ oxidation and fast crystallization which will cause poor film morphology, serious recombination and result in poor Voc and FF. To overcome these defects, additive engineering is introduced into the fabrication of Sn-based perovskites and has already achieved remarkable progress in improving opto-electrical performance through film morphology modification, crystallinity enhancement, defect passivation and band gap optimization. This review discussed the corresponding researches on additives which show outstanding efficacy to optimize the Voc and FF of Sn-based PSCs and it can be concluded that additives engineering has indispensable effect on achieving high performance Sn-based devices and the future development of Sn-based PSCs.